Mitogen-activated protein kinases (MAPKs) mediate SIN-1/glucose deprivation-induced death in rat primary astrocytes - Yoo, Byoung Kwon; Choi, Ji Woong; Choi, Min Sik; Ryu, Mi Kyoung; Park, Gyu Hwan; Jeon, Mi Jin; Ko, Kwang Ho (Archives of pharmacal research, 2005)
Peroxynitrite is a potent neurotoxic molecule produced from a reaction between NO and superoxide and induces NO-mediated inflammation under neuropathological conditions. Previously, we reported that glucose deprivation induced ATP depletion and cell death in immunostimulated astrocytes, which was mainly due to peroxynitrite. In this study, the role of MAPKs (ERK1/2, p38MAPK, and JNK1SAPK) signal pathway in the SIN-1/glucose deprivation-induced death of astrocytes was examined. A combined treatment with glucose deprivation and 50 microM SIN-1, an endogenous peroxynitrite generator, rapidly and markedly increased the death in rat primary astrocytes. Also, SIN-1/glucose deprivation resulted in the activation of MAPKs, which was significantly blocked by the treatment with 20 microM MAPKs inhibitors (ERK1/2, PD98059; p38MAPK, SB203580; JNK/SAPK, SP600125). Interestingly, SIN-1/glucose deprivation caused the loss of intracellular ATP level, which was significantly reversed by MAPKs inhibitors. These results suggest that the activation of MAPKs plays an important role in SIN-1/glucose deprivation-induced cell death by regulating the intracellular ATP level.